Pengaruh Inflasi Terhadap Pertumbuhan Ekonomi Di Indonesia - Meilan Sri Desfitra; Zahwa Aulia; Rezeki Putri Utami; Nur Fitriana (CV. ITTC INDONESIA, 2024)
This abstract discusses the influence of inflation on economic growth in Indonesia. In general, inflation is the phenomenon of a continuous and continuous increase in the prices of goods and services over a certain period of time. Economic growth, on the other hand, measures the increase in a country's gross domestic product (GDP) or national income over a certain period of time. This research explores the relationship between inflation and economic growth in Indonesia using secondary data from Bank Indonesia and the Central Statistics Agency for the 2010-2020 period. Data analysis shows that inflation has a significant impact on economic growth in Indonesia. The research results show that high inflation tends to hamper economic growth by reducing people's purchasing power, reducing investment and improving the economy. However, moderate inflation can encourage economic growth by encouraging stable consumption and investment. This study also identifies other factors that influence the relationship between inflation and economic growth, such as monetary policy, political stability, and external factors. The implications of this research are the importance of appropriate monetary policy to control inflation so that it does not hamper economic growth, as well as the need for balanced fiscal policy to create stable and sustainable macroeconomic conditions in Indonesia.